Dissociable Effects of Psychopathic Traits on Executive Functioning: Insights From the Triarchic Model - Pasion, Rita; Cruz, Ana R.; Barbosa, Fernando (Frontiers in Psychology, 2018)
The relationship between executive functioning and psychopathy lacks consistent findings. The heterogeneity of the psychopathic personality structure may contribute to the mixed data that emerged from clinical-categorical approaches. Considering the link between antisocial behavior and executive dysfunction from the perspective of the Triarchic Model of Psychopathy, it is suggested that executive impairments in psychopathy are specifically explained by meanness and disinhibition traits, reflecting externalizing vulnerability. In turn, boldness is conceptualized as an adaptive trait. The current study assessed updating (N-back), inhibition (Stroop), and shifting (Trail Making Test) in a forensic (n = 56) and non-forensic sample (n = 48) that completed the Triarchic Psychopathy Measure. A positive association between boldness and inhibition was found, while meanness accounted for the lack of inhibitory control. In addition, disinhibition explained updating dysfunction. These findings provide empirical evidence for dissociable effects of psychopathic traits on executive functioning, in light of the Triarchic Model of Psychopathy.